EFFECT OF HAIR TONIC COMBINATION OF CINNAMOMUN ESSENSIAL OIL AND CANDLENUT ESSENSIAL OIL HAIR GROWTH IN VIVO - Mutamimmah, Siti; Pratiwi, Elasari Dwi; Kusumo, Djati Wulan (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Hair loss, often called alopecia, is characterized by excessive hair loss. One way to treat hair loss is to use hair tonic preparation. This study aimed to determine the effect of a combination of hair tonic cinnamon essential oil and candlenut essential oil on hair growth. The research method used included physical evaluation of the hair tonic preparation formulation by examining the physical quality, homogeneity, pH, viscosity, and stability of the hair tonic preparation. The effectiveness of hair growth was evaluated in vivo in rabbits. Its effectiveness measures hair growth and weight. Based on the results of the tests on the physical characteristics and physical stability of the hair tonic preparation, a combination of cinnamon essential oil and candlenut essential oil at concentrations of 0% (F0), 2.5% (F1), 5% (F2), and 7.5% (F3) was used. in organoleptic testing, the homogeneity, pH, and viscosity met the specified characteristics and stability requirements. The results of research testing the effectiveness of hair growth showed that the hair tonic combination of cinnamon essential oil and candlenut essential oil is effective for good hair growth in formula 3, with a hair length of 8 mm and a hair mass of 213.8 mg on day 21. Keywords: Candlenut essential oil, Cinnamon essential oil, Hair growth, Hair tonic, In vivo